Effects of mitral valve regurgitation in the dog on the right ventricle - Todosijevic, Aleksandra (2011)
Introduction. Mitral regurgitation (MR) in dogs is characterised on radiographs by increasing size of the heart, called “general heart enlargement.” The appearance suggests that the right heart chambers may be enlarged, but there is no agreement on this, or if present, its cause. Concurrent enlargement of the right heart chambers in MR would have to be explained by pathophysiologic mechanisms that might affect prognosis and treatment.